Pembinaan dan Pendampingan Digital Marketing Destinasi Wisata Bukit Roso Wulan di Desa Giri Suko, Turunan, Panggang, Gunungkidul - Astuti, Marni; Mauidzoh, Uyuunul; Aryanto, Salam (Journal of Appropriate Technology for Community Services, 2025)
Bukit Roso Wulan is a tourism village managed by the Forest Farmers Group “Wana Lestari II,” located in Turunan Village, Giri Suko, Panggang, Gunung Kidul. In the Community Service activity under the Community-Based Empowerment scheme, the “Wana Lestari II” group serves as a partner of Insitut Teknologi Dirgantara Adisutjipto. The main issues identified are poor management and promotion in the development of Bukit Roso Wulan tourism village. The inadequate management is due to a lack of community awareness as tourism drivers, overlapping information and work/reporting procedures, and the difficulty in evaluating management processes. Meanwhile, promotional problems stem from limited skills in content creation and promotional management. Training related to business management and promotional strategies can enhance the capabilities of the group, thereby improving the governance capacity of Bukit Roso Wulan. Promotional issues are addressed by enhancing content creation techniques, promoting through social media, and evaluating promotional outcomes. The results of the community service activity include improved promotional skills using digital platforms with broader reach and more targeted audiences, as well as increased understanding of the importance of management and marketing for the sustainability of Bukit Roso Wulan tourism village.